The Psychological and Social Effects of Single Parenting on the Development of Children (International Journal of Scientific Research in Science and Technology, 2025)
The gender roles and structures of the traditional family have been muddled as a result of urbanization, industrialization, and modernity, challenging and continually changing long-held social ideas. Research from two to three decades ago indicated that children’s development can be adversely affected by familial instability. A child’s mental health is impacted by the absence or death of one parent, as well as by disputes between separated or divorced parents, physical health, overall development, and future relationships. Due to their lack of social support, societal shame, and heavy parenting load, single parents frequently find it difficult to spend quality time with their kids. As a result, single parent children struggle academically and engage in less social activities as well as emotional and behavioral issues. More recent studies have concentrated on the advantages and safeguards that can help a youngster achieve better results. In order to support the child’s adjustment both now and in the future, we must concentrate on these protective and resilience-building aspects.